Evaluasi Pengelolaan Keuangan Dana Desa Berdasarkan Permendagri Nomor 20 Tahun 2018 Di Desa Karang Sari Kecamatan Padang Ratu Lampung Tengah - Karnila Ali; Ardiansyah Japlani; Selvi Wahyu Puspita (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to determine the suitability of financial management of village funds in Karang Sari Village by analyzing data based on the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management, namely at the planning, implementation, administration, reporting, and accountability stages. The object of this research is Karang Sari Village, Padang Ratu District, Central Lampung. This research is qualitative with a descriptive analysis approach using 16 informants consisting of village officials and 8 hamlet heads. The research subjects were determined using purposive sampling techniques and data collection techniques consisted of observation, interviews and documentation. The data analysis used was reduction, triagulation, data display, and conclusion. In general, the problems found are the lack of knowledge in the management of funds and the lack of quality of human resources, the lack of assistance and the quality of assistance and the lack of supervision carried out in the management of village funds so that there is a gap in discrepancies in the financial management of village funds. Based on data analysis, this study states that the financial management of village funds in Karang Sari Village is not technically in accordance with Permendagri Number 20 of 2018, namely at the accountability stage there is no information on the 2023 village fund budget realization report which is conveyed to the public through information media and several obstacles are found in its implementation.